Brief notes on the Epistle to the Ephesians - Bellett, John Gifford, 1795-1864 (Denver, CO Wilson Foundation)
Compilation : Includes "The church at Thessalonica"
Brethren writer.
Keywords: Bible. N.T. Ephesians -- commentaries; Thessalonica, biblical church